Spinel lithium manganate, method for its production and use thereof
Patent Information
- Application Number
- CN202180087273.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-12-25
- Filing Date
- 2021-12-21
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2041-12-21
AI Technical Summary
[0005]然而,尖晶石型锰酸锂在高温稳定性、即高温下的充放电特性、特别是碳对电极充放电特性、保存特性上存在问题,期望解决该课题
[0029]对于本发明的尖晶石型锰酸锂,在将其用于锂二次电池用正极材料的情况下,可以提供与以往相比高温下的充放电特性、特别是碳对电极充放电特性优异、电阻小、功率特性优异的锂二次电池。
Smart Images

Figure BDA0004300207600000111 
Figure BDA0004300207600000112 
Figure HDA0004300207610000011
Abstract
Description
Technical Field
[0001] This invention relates to spinel-type lithium manganese oxide, its manufacturing method and its use, and more specifically to spinel-type lithium manganese oxide containing phosphate, its manufacturing method, and lithium secondary batteries obtained by using it as an electrode. Background Technology
[0002] Lithium-ion rechargeable batteries have a higher energy density than other rechargeable batteries, and are therefore widely used as batteries for portable devices. Furthermore, recent research is focused on further improving performance for larger applications requiring high capacity and high power, such as those for installation and automotive applications.
[0003] Currently, in the cathode materials of lithium-ion batteries, cobalt-based materials (LiCoO2) are mainly used in small batteries for consumer applications such as mobile phones, while nickel-based materials (LiNi) are mainly used in batteries for electrical installations and automotive applications. 0.8 Co 0.15 Al 0.05 O2), nickel-cobalt-manganese ternary materials (LiNi) 0.5 Co 0.2 Mn 0.3 (O2, etc.). However, cobalt and nickel raw materials are scarce and expensive, and their power characteristics are not very high.
[0004] On the other hand, manganese, the raw material for spinel-type lithium manganese oxide, which is one of the manganese-based materials, is abundant and inexpensive. In addition, it has excellent safety, making it one of the materials suitable for applications requiring large batteries.
[0005] However, spinel-type lithium manganese oxide has problems with high-temperature stability, i.e., charge-discharge characteristics at high temperatures, especially the charge-discharge characteristics of the carbon counter electrode, and storage characteristics. It is hoped that this problem can be solved. For example, both Patent Document 1 and Patent Document 2 propose spinel-type lithium manganese oxide containing phosphate, but there is room for improvement in the charge-discharge characteristics at high temperatures, especially the charge-discharge characteristics of the carbon counter electrode.
[0006] In addition, spinel-type lithium manganese oxide has excellent power characteristics, but further characteristic improvements are expected to develop batteries with power characteristics equivalent to capacitors and high energy density.
[0007] Existing technical documents
[0008] Patent documents
[0009] Patent Document 1: Japanese Patent No. 5556983
[0010] Patent Document 2: Japanese Patent Application Publication No. 2017-31006 Summary of the Invention
[0011] The problem the invention aims to solve
[0012] The purpose of this invention is to provide spinel-type lithium manganese oxide with excellent charge-discharge characteristics at high temperatures, especially with excellent charge-discharge characteristics of the carbon counter electrode, as well as low resistance and excellent power characteristics, and further to provide a lithium secondary battery using spinel-type lithium manganese oxide as the positive electrode.
[0013] Solution for solving the problem
[0014] The inventors have conducted repeated and in-depth research on spinel-type lithium manganese oxide. As a result, they discovered that the present invention, based on the following principles, can achieve the aforementioned objectives.
[0015] That is, the present invention is based on the following [1] to
[12] .
[0016] [1] A spinel-type lithium manganese oxide containing phosphate and using the chemical formula Li 1+X Mn 2-X-Y M Y O4 (where 0.02≤X≤0.20, 0.05≤Y≤0.30, and M is Al or Mg) indicates that the pore volume of the spinel-type lithium manganese oxide with a pore size of less than 0.6 μm is 0.003 cm³. 3 / g or more and 0.2cm 3 For particles smaller than / g, the relative standard deviation of the secondary particle size is greater than 25% and less than 45%.
[0017] [2] The spinel-type lithium manganese oxide described in [1] above has a phosphorus / manganese molar ratio of 0.0015 or more and 0.1 or less.
[0018] [3] The spinel-type lithium manganese oxide described in [1] or [2] above has a BET specific surface area of 0.8 m². 2 / g or more and 5.0m 2 / g or less.
[0019] [4] The spinel-type lithium manganese oxide according to any one of [1] to [3] above, wherein the average particle size of the secondary particles is 4 μm or more and 20 μm or less.
[0020] [5] The spinel-type lithium manganese oxide according to any one of [1] to [4] above, wherein the content of SO4 is 0.8 wt% or less.
[0021] [6] The spinel-type lithium manganese oxide according to any one of [1] to [5] above, wherein the Na content is less than 3000 wtppm.
[0022] [7] The spinel-type lithium manganese oxide according to any one of [1] to [6] above, wherein the boron content is less than 100 wtppm.
[0023] [8] The spinel-type lithium manganese oxide according to any one of [1] to [7] above, wherein the DC resistance of the CR2032 type coin cell with Li counter electrode is 25Ω or less at 50% charge.
[0024] [9] A method for manufacturing spinel-type lithium manganese oxide according to any one of [1] to [8] above, wherein a manganese compound, a lithium compound, a compound containing the M element as described in technical solution 1, a phosphoric acid compound and a boron compound are added to a solution to prepare a slurry in which the mixture of the above is dispersed, and the slurry, which has an average particle size of less than 1 μm, is granulated by spray drying and then calcined and crushed in the atmosphere or in a high concentration oxygen atmosphere (including a pure oxygen atmosphere) at a temperature of 700°C or higher and 960°C or lower.
[0025]
[10] In the method for manufacturing spinel-type lithium manganese oxide described above [9], boron is removed to below 100 wtppm by washing with water after calcination.
[0026]
[11] An electrode comprising any one of the spinel-type lithium manganese oxide described in any one of [1] to [8] above.
[0027]
[12] A lithium secondary battery that uses the electrode described in
[11] above as the positive electrode.
[0028] The effects of the invention
[0029] When the spinel-type lithium manganese oxide of the present invention is used as a cathode material for lithium secondary batteries, it can provide lithium secondary batteries with superior charge-discharge characteristics at high temperatures, especially the charge-discharge characteristics of the carbon counter electrode, as well as low resistance and excellent power characteristics compared with the past. Attached Figure Description
[0030] Figure 1 The pore distribution of the spinel-type lithium manganese oxide containing phosphate obtained in Example 1 is shown. Detailed Implementation
[0031] The present invention will now be described in detail.
[0032] The spinel-type lithium manganese oxide of the present invention contains a phosphate. The phosphate is not particularly limited, and examples include lithium phosphates such as Li3PO4 and LiPO3, sodium phosphates such as Na3PO4, NaH2PO4, and Na2HPO4, and potassium phosphates such as K3PO4, KH2PO4, and K2HPO4. Li3PO4 and LiPO3 are preferred, and Li3PO4 is more preferred. When the phosphate is included in the spinel-type lithium manganese oxide and used as a positive electrode active material in a lithium secondary battery, it exhibits excellent charge-discharge characteristics at high temperatures. The properties of the contained phosphate are not particularly limited, and examples include crystalline, crystalline and porous, crystalline and dense, amorphous, amorphous and porous, and amorphous and dense, but it is not limited to these.
[0033] The spinel-type lithium manganese oxide of the present invention uses the chemical formula Li 1+X Mn 2-X-Y M Y O4 (where 0.02≤X≤0.20, 0.05≤Y≤0.30, and M is Al or Mg) represents this. If the value of X is below 0.02, it easily leads to a decrease in capacity during charging and discharging at high temperatures; if it exceeds 0.20, sufficient charge-discharge capacity cannot be obtained. Similarly, if the value of Y is below 0.05, it easily leads to a decrease in capacity during charging and discharging at high temperatures; if it exceeds 0.30, sufficient charge-discharge capacity cannot be obtained. X and Y of spinel-type lithium manganese oxide can be determined by compositional analysis. Examples of such methods include inductively coupled plasma atomic absorption spectrometry (ICP-AAS) and atomic absorption spectrometry.
[0034] The spinel-type lithium manganese oxide of the present invention has a pore volume of 0.003 cm³ for pores with a diameter of 0.6 μm or less. 3 / g or more and 0.2cm 3 / g or less. By making the pore volume of pores with a diameter of 0.6μm or less 0.003cm³. 3 / g or more and 0.2cm 3 When used as a positive electrode in lithium-ion secondary batteries with a particle size of less than 0.6 μm, the spinel-type lithium manganese oxide particles contain electrolyte. This increases the contact area between the spinel-type lithium manganese oxide particles and the electrolyte, thus reducing resistance and improving power characteristics. However, if the pore volume of pores with a diameter of less than 0.6 μm becomes less than 0.003 cm³, the... 3 If the electrolyte content inside the spinel-type lithium manganese oxide secondary particles becomes insufficient ( / g), the contact area between the spinel-type lithium manganese oxide particles and the electrolyte decreases, the resistance increases, and consequently, the power characteristics tend to deteriorate, making this undesirable. Furthermore, if the pore volume of pores with a diameter of less than 0.6 μm becomes greater than 0.2 cm³, the electrolyte concentration will also be affected. 3If the density of the positive electrode is reduced to a certain value (e.g., g), the electrolyte content inside the spinel-type lithium manganese oxide secondary particles increases, leading to a larger contact area between the particles and the electrolyte. This makes manganese leaching more likely, resulting in decreased high-temperature durability when used as a positive electrode in lithium-ion secondary batteries. Therefore, this method is not preferred. The pore volume of pores with a diameter of 0.6 μm or less is preferably 0.004 cm³. 3 / g or more and 0.15cm 3 / g or less, more preferably 0.015cm 3 / g or more and 0.1cm 3 / g or less. The pore volume of spinel-type lithium manganese oxide can be determined by mercury porosimetry.
[0035] The relative standard deviation of the secondary particle size of the spinel-type lithium manganese oxide of the present invention is 25% or more and 45% or less. By making the relative standard deviation of the secondary particle size 25% or more and 45% or less, the particle size distribution of the secondary particles becomes sharp. As a result, when used as a positive electrode of a lithium-ion secondary battery, the mixing uniformity of the spinel-type lithium manganese oxide with the conductive agent and binder is improved, the charge-discharge cycle characteristics are improved, and the resistance is reduced. The relative standard deviation of the secondary particle size is preferably 25% or more and 40% or less, more preferably 27% or more and 35% or less.
[0036] When the spinel-type lithium manganese oxide of the present invention is used as the positive electrode active material of a lithium secondary battery, in order to enable the reaction of capturing trace amounts of hydrogen fluoride contained in the electrolyte of the lithium secondary battery by phosphate to proceed rapidly, as a result, the manganese dissolution caused by the reaction of hydrogen fluoride with spinel-type lithium manganese oxide is further suppressed, and the capacity reduction during charging and discharging at high temperature is further suppressed. The phosphorus / manganese molar ratio is preferably 0.0015 or more and 0.1 or less, more preferably 0.002 or more and 0.05 or less.
[0037] When the spinel-type lithium manganese oxide of the present invention is used as the positive electrode active material of a lithium secondary battery, in order to obtain excellent charge-discharge characteristics at high temperatures, reduce resistance, and obtain better power characteristics, the BET specific surface area is preferably 0.8 m². 2 / g or more and 5.0m 2 / g or less, more preferably 1.0m 2 / g or more and 4.0m 2 / g or less.
[0038] When the spinel-type lithium manganese oxide of the present invention is used as the positive electrode active material of a lithium secondary battery, in order to reduce the lithium diffusion distance within the spinel-type lithium manganese oxide particles, obtain better power characteristics, and further improve the filling capacity of the positive electrode agent, the average particle size of the secondary particles is preferably 4 μm or more and 20 μm or less, more preferably 5 μm or more and 10 μm or less.
[0039] For the spinel-type lithium manganese oxide of the present invention, in order to further increase the charge and discharge capacity when used as the positive electrode active material of lithium secondary batteries and to obtain better charge and discharge characteristics at high temperatures, the content of SO4 is preferably 0.8 wt% or less, more preferably 0.5 wt% or less.
[0040] For the spinel-type lithium manganese oxide of the present invention, in order to further increase the charge and discharge capacity when used as the positive electrode active material of lithium secondary batteries, improve crystallinity, and obtain better charge and discharge characteristics at high temperature, the Na content is preferably 3000 wtppm or less, more preferably 1500 wtppm or less, and even more preferably 1000 wtppm or less.
[0041] Next, the method for manufacturing spinel-type lithium manganese oxide of the present invention will be described.
[0042] The spinel-type lithium manganese oxide of the present invention is obtained as follows: a manganese compound, a lithium compound, a compound containing element M as described in technical solution 1, a phosphoric acid compound, and a boron compound are added to a solution to prepare a slurry in which the mixture is dispersed. The slurry, with an average particle size of 1 μm or less, is then granulated by spray drying and calcined in air or in a high-concentration oxygen atmosphere (including a pure oxygen atmosphere) at a temperature of 700°C or higher and 960°C or lower, followed by crushing, thereby obtaining the product. If the average particle size of the mixture exceeds 1 μm, the pore volume of pores with a pore size of 0.6 μm or less easily becomes less than 0.003 cm³. 3 .
[0043] Manganese compounds, lithium compounds, compounds containing element M as described in technical solution 1, phosphoric acid compounds, and boron compounds can all be water-soluble substances.
[0044] There are no particular restrictions on manganese compounds, such as electrolytic manganese dioxide, Mn3O4, Mn2O3, etc., but they are not limited to these.
[0045] There are no particular restrictions on lithium compounds, such as lithium carbonate, lithium hydroxide, lithium nitrate, lithium chloride, lithium iodide, lithium oxalate, etc., but they are not limited to these.
[0046] Phosphoric acid compounds are not particularly limited, and examples include lithium phosphates such as Li3PO4 and LiPO3, sodium phosphates such as Na3PO4, NaH2PO4, and Na2HPO4, potassium phosphates such as K3PO4, KH2PO4, and K2HPO4, magnesium phosphates such as Mg3(PO4)2, MgHPO4, and Mg(H2PO4)2, ammonium phosphates such as NH4H2PO4 and (NH4)2HPO4, and hydrogen phosphates such as H3PO4, but are not limited to these.
[0047] There are no particular limitations on compounds containing the M (Al or Mg) element described in technical solution 1. Examples include Al(OH)3, AlOOH, Al2O3, Mg(OH)2, MgO, etc., but these are not limited to them.
[0048] There are no particular restrictions on boron compounds, such as H3BO3, B2O3, Li2O·nB2O3 (n=1~5), etc., but they are not limited to these.
[0049] Regarding the slurry containing a mixture of manganese compound, lithium compound, compound containing element M as described in technical solution 1, phosphoric acid compound, and boron compound, the average particle size of the mixture is 1 μm or less, but preferably 0.3 μm or more and 0.7 μm or less. This average particle size is obtained by adding the compound to the solution and then pulverizing and mixing it. For example, a wet media stirring mill, ball mill, or vibratory mill can be used as the pulverizing and mixing device. The manganese compound, lithium compound, compound containing element M as described in technical solution 1, phosphoric acid compound, and boron compound may be partially or completely dissolved in water.
[0050] Solutions in which a compound is added can be exemplified by, for example, pure water, water, etc.
[0051] The slurry obtained by wet grinding and mixing is granulated by spray drying. In spray drying, conventional spray dryers can be used, such as those that spray the slurry with a rotating disc or fluid nozzle and those that dry the droplets with hot air.
[0052] The calcination for obtaining the spinel-type lithium manganese oxide of the present invention is carried out in the atmosphere or in a high-concentration oxygen atmosphere (including a pure oxygen atmosphere), i.e., an oxygen atmosphere with an oxygen content of 18 to 100 vol%, at a temperature of 700°C or higher and 960°C or lower. At temperatures lower than 700°C, the pore volume of the spinel-type lithium manganese oxide with a pore size of 0.6 μm or less becomes excessively large, making it easier to reduce the density when using the spinel-type lithium manganese oxide as a positive electrode. If the temperature exceeds 960°C, the oxygen defects in the spinel-type lithium manganese oxide increase, resulting in a tendency for the charge-discharge cycle characteristics to decrease when used as a positive electrode active material in lithium secondary batteries. Calcination is preferably carried out at a temperature of 750°C or higher and 850°C or lower.
[0053] The spinel-type lithium manganese oxide of the present invention is preferably washed with water to remove boron compounds in order to improve charge-discharge cycle characteristics and reduce resistance. Preferably, the boron compounds are removed to below 100 wtppm by water washing.
[0054] Spinel-type lithium manganese oxide particles tend to agglomerate during sintering; therefore, crushing is preferred to achieve the target particle size. The crushing method is preferably shear-force based crushing to further suppress the formation of fine powder.
[0055] After crushing spinel-type lithium manganese oxide, it is preferable to sieve it to remove coarse particles that exceed the thickness of the positive electrode. The sieve aperture is preferably 200 μm or less, more preferably 150 μm or less.
[0056] By using the spinel-type lithium manganese oxide containing phosphate of the present invention as the positive electrode of a lithium secondary battery, it is possible to construct a lithium secondary battery that is previously unattainable, exhibiting excellent charge-discharge cycle characteristics at high temperatures, low resistance, and excellent power characteristics.
[0057] There are no particular limitations on the composition of the lithium secondary battery other than the positive electrode. Examples of negative electrodes include materials that absorb, store, and release Li, such as carbon-based materials, tin oxide-based materials, and Li₄Ti₅O₂. 12 Materials that form alloys with Li, such as SiO, etc. Examples of materials that form alloys with Li include silicon-based materials and aluminum-based materials. Examples of electrolytes include organic electrolytes containing Li salts dissolved in organic solvents and various additives, solid electrolytes with Li ion conductivity, and electrolytes composed of combinations of these.
[0058] Example
[0059] Next, specific embodiments will be used to illustrate the present invention, but the present invention is not limited to these embodiments.
[0060] <Compositional analysis, determination of SO4 content, Na content, and boron content>
[0061] Regarding the composition, SO4 content, Na content, and boron content of the spinel-type lithium manganese oxide obtained in the examples and comparative examples, the spinel-type lithium manganese oxide was dissolved in a hydrochloric acid-hydrogen peroxide mixed aqueous solution and analyzed using an inductively coupled plasma atomic emission spectrometer (trade name: ICP-AES, manufactured by PerkinElmer Japan).
[0062] <Determination of pore volume>
[0063] For the spinel-type lithium manganese oxide obtained in the examples and comparative examples, the pore volume was measured using an automatic mercury porosimeter pore distribution measuring device (trade name: AutoPore V9600, manufactured by MICROMERITICS). The mercury porosimeter pressure was set to 0.48–33000 psia.
[0064] <Determination of BET specific surface area>
[0065] Place 1.0g of the sample into a glass cuvette for BET surface area determination, and dehydrate it at 150°C for 30 minutes under a nitrogen flow to remove the moisture adhering to the powder particles.
[0066] For the treated sample, the BET specific surface area was determined by single-point method using a mixed gas of 30% nitrogen and 70% helium as the adsorbent in a BET measuring apparatus (trade name: MICROMERITICS DeSorbIII, manufactured by Shimadzu Corporation).
[0067] <Determination of the average particle size and relative standard deviation of secondary particle size>
[0068] The average particle size (D) of secondary particles of lithium manganese oxide was determined using a particle size distribution measuring device (trade name: MT3000II series, manufactured by MicrotracBEL). 50 ) and the standard deviation of particle size.
[0069] The relative standard deviation of the secondary particle size is calculated based on the following formula using the measured average particle size and standard deviation of the secondary particles.
[0070] Relative standard deviation (%) = (Standard deviation of particle size) / (Average particle size) × 100
[0071] <Determination of initial capacity and DC resistance>
[0072] Regarding the positive electrode, 1.0 g of spinel-type lithium manganese oxide obtained in the examples and comparative examples was mixed with 0.032 g of acetylene black (trade name: DENKA BLACK, manufactured by DENKA), 0.307 mL of 10 wt% polyvinylidene fluoride / N-methyl-2-pyrrolidone solution (0.032 g of polyvinylidene fluoride), and 0.751 mL of N-methyl-2-pyrrolidone (by weight, the ratio of spinel-type lithium manganese oxide: acetylene black: polyvinylidene fluoride = 94:3:3) in a rotary mixer (trade name: AR-100, manufactured by THINKY CORPORATION) to prepare a positive electrode material slurry. The obtained positive electrode material slurry was coated onto aluminum foil, dried at 150°C for 30 minutes, and then punched into pieces with a diameter of 15.958 mm at a density of 3 ton / cm. 2 The mixture is subjected to uniaxial pressing and dried under reduced pressure at 150°C for 2 hours before use. The coating amount is set to achieve a spinel-type lithium manganese oxide content of 5 mg / cm³. 2 .
[0073] As the negative electrode, a Li foil cut to a diameter of 16 mm is used, dissolved in a mixed solvent of ethylene carbonate and dimethyl carbonate (volume ratio 1:2) containing 1 mol / dm³. 3 The LiPF6 electrolyte and separator (trade names: Celgard, Polypore) are used to manufacture the CR2032 coin cell battery.
[0074] Using the manufactured battery, perform one charge-discharge cycle at 24°C, between 4.3V and 3.0V, with a current of 0.1mA, and use the discharge capacity as the initial capacity.
[0075] Next, charging was performed until 50% of the initial capacity was reached, and the DC resistance was measured at 24°C. Regarding the DC resistance, the circuit was charged at 2mA for 10 seconds, the closed-circuit voltage was measured, then discharged at 0.2mA for 100 seconds and stopped for 1 hour. Then, the circuit was charged at 5mA for 10 seconds, the closed-circuit voltage was measured, then discharged at 0.2mA for 250 seconds and stopped for 1 hour. Then, the circuit was charged at 10mA for 10 seconds, the closed-circuit voltage was measured, then discharged at 0.2mA for 500 seconds and stopped for 1 hour. The closed-circuit voltage relative to each current value was plotted, and the slope was taken as the DC resistance.
[0076] <Carbon counter electrode charge-discharge cycle test>
[0077] The positive electrode uses the same electrode as the one used in the initial capacity determination.
[0078] Regarding the negative electrode, 2.0 g of spheroidized natural graphite was mixed with 2.104 mL of a 10 wt% polyvinylidene fluoride / N-methyl-2-pyrrolidone solution (0.221 g of polyvinylidene fluoride) (graphite:polyvinylidene fluoride = 90:10 by weight) in a rotary mixer (trade name: AR-100, manufactured by THINKY CORPORATION) to prepare a negative electrode material slurry. The obtained negative electrode material slurry was coated onto copper foil, dried at 150°C for 30 minutes, and then punched into pieces with a diameter of 16.156 mm at a rate of 3 ton / cm. 2 Uniaxial pressing was performed, followed by vacuum drying at 150°C for 2 hours before use. The coating amount was set to achieve a spheroidized natural graphite concentration of 1.8 mg / cm³. 2 .
[0079] Using positive and negative electrodes, a solution of 1 mol / dm³ was dissolved in a mixed solvent of ethylene carbonate and dimethyl carbonate (volume ratio 1:2). 3 CR2032 type coin cell battery was made by using 0.2 mL of electrolyte obtained from LiPF6 and separator (trade name: Celgard, manufactured by Polypore).
[0080] Using the fabricated battery, one constant-current constant-voltage charge-discharge cycle was performed at 24°C with a current of 0.1mA between the cell voltages of 4.25V and 3.0V. Then, another constant-current constant-voltage charge-discharge cycle was performed at 24°C with a current of 0.2mA between the cell voltages of 4.25V and 3.0V, and the discharge capacity was taken as the cell capacity. Next, 50 constant-current constant-voltage charge-discharge cycles were performed at 45°C with the cell voltages of 4.25V and 3.0V, at a current density equal to the 1-hour discharge rate relative to the cell capacity. The cycle maintenance rate of the carbon counter electrode was calculated by the ratio of the discharge capacity of the 50th cycle to that of the 1st cycle. It should be noted that the constant-voltage charging was terminated when the charging current decayed to 1 / 10 of the initial constant-current charging value.
[0081] Example 1
[0082] In pure water, 374g of lithium carbonate, 1533g of electrolytic manganese dioxide, 73g of aluminum hydroxide, 15g of trilithium phosphate, and 3g of boric acid were added to prepare a 10L slurry. The slurry was then pulverized for 3 hours in a pulverizer (trade name: DYNO-MILL, manufactured by Shinmaru Enterprises Corporation). The average particle size (Dm) of the mixture of lithium carbonate, electrolytic manganese dioxide, aluminum hydroxide, trilithium phosphate, and boric acid was determined using a particle size distribution measuring device (trade name: MT3000II series, manufactured by MicrotracBEL). 50 The result was 0.6 μm. The resulting slurry was then dried using a spray dryer (Okawara Chemical Machinery) to evaporate the water, yielding spherical dried particles. Spray drying was performed at a hot air inlet temperature of 250°C.
[0083] For 300g of granulated dried particles, calcination was carried out in a box furnace at 750°C for 6 hours with air flowing at a rate of 5L / min, followed by cooling to room temperature. The heating rate was set to 100°C / hour, and the cooling rate was set to 20°C / hour from 800°C to 600°C and 100°C / hour from 600°C to room temperature. Next, pure water was added and stirred for 1 hour. After filtration, the particles were dried at 150°C and then crushed using a high-power small pulverizer (trade name: Rotary crusher, manufactured by OSAKA CHEMICAL Co., Ltd.) to pass them through a 150μm sieve, yielding spinel-type lithium manganese oxide containing phosphate.
[0084] The obtained phosphate-containing spinel-type lithium manganese oxide has the following composition: Li 1.10 Mn 1.80 Al 0.10O4. Furthermore, according to XRD analysis, the obtained spinel-type lithium manganese oxide containing phosphate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The results of the determination of phosphorus / manganese molar ratio, pore volume of pores with a diameter of 0.6 μm or less, BET specific surface area, average particle size of secondary lithium manganese oxide particles, relative standard deviation of secondary lithium manganese oxide particle size, SO4 content, Na content, and B content (hereinafter referred to as the determination results) are shown in Table 1, and the battery performance is shown in Table 2.
[0085] [Table 1]
[0086]
[0087] [Table 2]
[0088]
[0089] The pore distribution of phosphate-containing spinel-type lithium manganese oxide is shown in... Figure 1 .
[0090] Example 2
[0091] The amount of boric acid was 0.6 g, and the firing temperature was 900 °C. Otherwise, spinel-type lithium manganese oxide containing phosphate was obtained by the same method as in Example 1.
[0092] The obtained phosphate-containing spinel-type lithium manganese oxide has the following composition: Li 1.09 Mn 1.81 Al 0.10 O4. Furthermore, according to XRD analysis, the obtained spinel-type lithium manganese oxide containing phosphate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The measurement results are shown in Table 1, and the battery performance is shown in Table 2.
[0093] Example 3
[0094] The firing temperature was set to 800°C, and the spinel-type lithium manganese oxide containing phosphate was obtained using the same method as in Example 1.
[0095] The obtained phosphate-containing spinel-type lithium manganese oxide has the following composition: Li 1.10 Mn 1.80 Al 0.10 O4. Furthermore, according to XRD analysis, the obtained spinel-type lithium manganese oxide containing phosphate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The measurement results are shown in Table 1, and the battery performance is shown in Table 2.
[0096] Example 4
[0097] The firing temperature was set to 900°C, and the spinel-type lithium manganese oxide containing phosphate was obtained using the same method as in Example 1.
[0098] The obtained phosphate-containing spinel-type lithium manganese oxide has the following composition: Li 1.11 Mn 1.79 Al 0.10 O4. Furthermore, according to XRD analysis, the obtained spinel-type lithium manganese oxide containing phosphate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The measurement results are shown in Table 1, and the battery performance is shown in Table 2.
[0099] Example 5
[0100] The amount of trilithium phosphate was 31g, the amount of boric acid was 1g, and the firing temperature was 810°C. Otherwise, spinel-type lithium manganese oxide containing phosphate was obtained by the same method as in Example 1.
[0101] The obtained phosphate-containing spinel-type lithium manganese oxide has the following composition: Li 1.09 Mn 1.81 Al 0.10 O4. Furthermore, according to XRD analysis, the obtained spinel-type lithium manganese oxide containing phosphate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The measurement results are shown in Table 1, and the battery performance is shown in Table 2.
[0102] Example 6
[0103] The amount of trilithium phosphate was 46g. Otherwise, spinel-type lithium manganese oxide containing phosphate was obtained by the same method as in Example 5.
[0104] The obtained phosphate-containing spinel-type lithium manganese oxide has the following composition: Li 1.09 Mn 1.81 Al 0.10 O4. Furthermore, according to XRD analysis, the obtained spinel-type lithium manganese oxide containing phosphate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The measurement results are shown in Table 1, and the battery performance is shown in Table 2.
[0105] Example 7
[0106] In pure water, 356 g of lithium carbonate, 1577 g of electrolytic manganese dioxide, 53 g of magnesium hydroxide, 47 g of trilithium phosphate, and 1.7 g of boric acid were added to prepare a 10 L slurry. The slurry was then pulverized for 3 hours in a pulverizer (trade name: DYNO-MILL, manufactured by Shinmaru Enterprises Corporation). The average particle size (Dm) of the mixture of lithium carbonate, electrolytic manganese dioxide, magnesium hydroxide, trilithium phosphate, and boric acid was determined using a particle size distribution measuring device (trade name: MT3000II series, manufactured by MicrotracBEL). 50 The result was 0.6 μm. The resulting slurry was then dried using a spray dryer (Okawara Chemical Machinery) to evaporate the water, yielding spherical dried particles. Spray drying was performed at a hot air inlet temperature of 250°C.
[0107] For 300g of dried granules, calcination was carried out in a box furnace at 775°C for 6 hours with air flowing at a rate of 5L / min, followed by cooling to room temperature. The heating rate was set to 100°C / hour, and the cooling rate was set to 20°C / hour from 7750°C to 600°C and 100°C / hour from 600°C to room temperature. Next, pure water was added and stirred for 1 hour. After filtration, the mixture was dried at 150°C and then crushed using a high-power small pulverizer (trade name: Rotary crusher, manufactured by OSAKA CHEMICAL Co., Ltd.) to pass it through a 150μm sieve to obtain spinel-type lithium manganese oxide containing phosphate.
[0108] The obtained phosphate-containing spinel-type lithium manganese oxide has the following composition: Li 1.07 Mn 1.83 Mg 0.10 O4. Furthermore, according to XRD analysis, the obtained spinel-type lithium manganese oxide containing phosphate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The measurement results are shown in Table 1, and the battery performance is shown in Table 2.
[0109] Example 8
[0110] The amount of trilithium phosphate was 63g, the firing temperature was 800°C, and the spinel-type lithium manganese oxide containing phosphate was obtained by the same method as in Example 7.
[0111] The obtained phosphate-containing spinel-type lithium manganese oxide has the following composition: Li 1.07 Mn 1.83 Mg 0.10O4. Furthermore, according to XRD analysis, the obtained spinel-type lithium manganese oxide containing phosphate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The measurement results are shown in Table 1, and the battery performance is shown in Table 2.
[0112] Example 9
[0113] The amount of trilithium phosphate was 31g, the firing temperature was 800°C, and the spinel-type lithium manganese oxide containing phosphate was obtained by the same method as in Example 7.
[0114] The obtained phosphate-containing spinel-type lithium manganese oxide has the following composition: Li 1.06 Mn 1.84 Mg 0.10 O4. Furthermore, according to XRD analysis, the obtained spinel-type lithium manganese oxide containing phosphate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The measurement results are shown in Table 1, and the battery performance is shown in Table 2.
[0115] Example 10
[0116] The amount of trilithium phosphate was 62g, the firing temperature was 850°C, and the spinel-type lithium manganese oxide containing phosphate was obtained by the same method as in Example 7.
[0117] The obtained phosphate-containing spinel-type lithium manganese oxide has the following composition: Li 1.07 Mn 1.80 Mg 0.10 O4. Furthermore, according to XRD analysis, the obtained spinel-type lithium manganese oxide containing phosphate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The measurement results are shown in Table 1, and the battery performance is shown in Table 2.
[0118] Example 11
[0119] The amount of trilithium phosphate was 62g, the amount of boric acid was 2.8g, and the firing temperature was 850°C. Otherwise, spinel-type lithium manganese oxide containing phosphate was obtained by the same method as in Example 7.
[0120] The obtained phosphate-containing spinel-type lithium manganese oxide has the following composition: Li 1.06 Mn 1.84 Mg 0.10O4. Furthermore, according to XRD analysis, the obtained spinel-type lithium manganese oxide containing phosphate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The measurement results are shown in Table 1, and the battery performance is shown in Table 2.
[0121] Comparative Example 1
[0122] Without the addition of trilithium phosphate, spinel-type lithium manganese oxide was obtained using the same method as in Example 3.
[0123] The obtained spinel-type lithium manganese oxide has the following composition: Li 1.10 Mn 1.80 Al 0.10 O4. Furthermore, according to XRD analysis, the obtained spinel-type lithium manganese oxide is JCPDS No. 35-782 (LiMn2O4) single-phase. The measurement results are shown in Table 1, and the battery performance is shown in Table 2.
[0124] Comparative Example 2
[0125] 300g of electrolytic manganese dioxide (average particle size 3μm), 71g of lithium carbonate (average particle size 3μm), 6g of magnesium hydroxide (average particle size 2μm), and 3g of trilithium phosphate (average particle size 3μm) were dry-mixed and then calcined in a box furnace at 930°C for 6 hours with air flowing at a rate of 5L / min, followed by cooling to room temperature. The heating rate was set to 100°C / hour, and the cooling rate was set to 20°C / hour from 900°C to 600°C and 100°C / hour from 600°C to room temperature. Next, the mixture was crushed using a high-power small pulverizer (trade name: Rotary crusher, manufactured by OSAKA CHEMICAL Co., Ltd.) and passed through a 32μm sieve to obtain spinel-type lithium manganese oxide containing phosphate.
[0126] The obtained phosphate-containing spinel-type lithium manganese oxide has the following composition: Li 1.12 Mn 1.82 Mg 0.06 O4. Furthermore, according to XRD analysis, the obtained spinel-type lithium manganese oxide containing phosphate was a mixed phase of JCPDS No. 35-782 (LiMn2O4) and No. 25-1030 (Li3PO4). The measurement results are shown in Table 1, and the battery performance is shown in Table 2.
[0127] It should be noted that the entire contents of the specification, claims, drawings and abstract of Japanese Patent Application No. 2020-216330, filed on December 25, 2020, are incorporated herein as disclosure of the specification of this invention.
[0128] Industrial availability
[0129] The phosphate-containing spinel-type lithium manganese oxide of the present invention has pores with pore volume and secondary particle size, and therefore can be used as a positive electrode active material for lithium secondary batteries with excellent charge-discharge characteristics at high temperatures, especially excellent charge-discharge characteristics of carbon counter electrode, and excellent power characteristics.
Claims
1. A spinel-type lithium manganese oxide containing phosphate and formulated with the chemical formula Li 1+X Mn 2-X-Y M Y O4 represents the formula, where 0.02≤X≤0.20, 0.05≤Y≤0.30, M is Al or Mg, and the pore volume of the spinel-type lithium manganese oxide with a pore size of less than 0.6μm is 0.003cm³. 3 / g or more and 0.2cm 3 For particles smaller than / g, the relative standard deviation of the secondary particle size is greater than 27% and less than 45%. Its phosphorus / manganese molar ratio is greater than 0.0065 and less than 0.
05.
2. The spinel-type lithium manganese oxide according to claim 1, has a BET specific surface area of 0.8 m². 2 / g or more and 5.0m 2 / g or less.
3. The spinel-type lithium manganese oxide according to claim 1 or 2, wherein, The average particle size of the secondary particles is greater than 4 μm and less than 20 μm.
4. The spinel-type lithium manganese oxide according to claim 1 or 2, wherein, The SO4 content is less than 0.8 wt%.
5. The spinel-type lithium manganese oxide according to claim 1 or 2, wherein, The Na content is below 3000 wtppm.
6. The spinel-type lithium manganese oxide according to claim 1 or 2, wherein, The boron content is below 100 wtppm.
7. The spinel-type lithium manganese oxide according to claim 1 or 2, wherein, In the CR2032 type coin cell with Li counter electrode, the DC resistance at 50% charge is less than 25Ω.
8. A method for manufacturing spinel-type lithium manganese oxide according to any one of claims 1 to 7, wherein, A slurry containing a mixture of manganese, lithium, a compound containing element M as described in claim 1, a phosphoric acid compound, and a boron compound is prepared by adding manganese compound, lithium compound, compound containing element M as described in claim 1, phosphoric acid compound, and boron compound to a solution. The slurry, having an average particle size of less than 1 μm, is then granulated by spray drying and calcined and crushed in the atmosphere or in a high-concentration oxygen atmosphere containing only oxygen at a temperature of 700°C to 960°C.
9. The method for manufacturing spinel-type lithium manganese oxide according to claim 8, wherein, After firing, boron is removed to below 100 wtppm by washing with water.
10. An electrode comprising spinel-type lithium manganese oxide according to any one of claims 1 to 7.
11. A lithium secondary battery, wherein the electrode of claim 10 is used as the positive electrode.
Citation Information
Patent Citations
Lithium manganese composite oxide powder and production method therefor
JP2017031006A
Lithium manganate for nonaqueous electrolyte secondary battery, method for producing the same, and nonaqueous electrolyte secondary battery
CN101910066A
Positive electrode active material for non-aqueous electrolyte secondary batteries and its manufacturing method; non-aqueous electrolyte secondary batteries
CN102282701A
Lithium-manganese composite oxide granular secondary particle, method for production thereof and use thereof
CN1633394A
Lithium-manganese composite oxide powder and method for producing the same, and positive electrode for nonaqueous electrolyte secondary battery
JP2018095529A